Women in Chemistry: Exploring Their Contributions to the Development of Chemical Science - Abida Naja Putri; Agni Jamal; Arimby Anindya Putri; Dela Puspita Sari; Erma Ulifatulatifah; Fathimah Thohirotunnisa; Lenthamina Galuh Rahmawati; Nada Shafa Yusriyyah; Rahmadina Putri Herdianto; Vindy Sabina Putri; Habiddin Habiddin (PT Ahan Group Publisher, 2025)
The role of women in chemistry has undergone significant changes throughout history despite facing various social and cultural challenges. In the past, men dominated chemistry, and female scientists' contributions were often overlooked or minimized. However, over time, women have increasingly demonstrated their outstanding contributions to the development of chemistry. Names like Marie Curie, who won two Nobels in physics and chemistry, and Rosalind Franklin, who was instrumental in the discovery of the structure of DNA, are undeniable proof that women have a crucial role to play in the advancement of chemistry. However, gender stereotypes and social norms often limit women's career options in science, and the influence of an academic environment that does not always support gender equality hinders their potential to develop fully. In addition, women are often faced with dual challenges, such as the double burden of managing a scientific career and family responsibilities. Based on these challenges, developing more inclusive and supportive policies and strategies is imperative to enable more women to engage in chemistry. In addition, creating a flexible work environment that prioritizes work-life balance will help reduce barriers for women in developing a career in chemistry. This research aims to trace the long journey of women in chemistry, identify the obstacles they face, and explore solutions and steps that can be taken to realize gender equality in this field. With these steps, it can be ensured that the full potential of women in chemistry can be realized so that they can contribute to advancing global science and technology more broadly.